A Novel Approach on Teaching Network Security for ICT Courses - Md Khambari, M. N.; Othman, M. F. I.; Motsidi, M. R.; Abdollah, M. F. (2009)
This paper discusses a curriculum approach that will give emphasis on practical sessions of teaching network security subjects in information and communication technology courses. As we are well aware, the need to use a practice and application oriented approach in education is paramount [1]. Research on active learning and cooperative groups showed that students grasps and have more tendency towards obtaining and realizing soft skills like leadership, communication and team work as opposed to learning using the traditional theory and exam based method. While this teaching and learning paradigm is relatively new in Malaysia, it has been practiced widely in the West. This paper examines a particular approach whereby students learning wireless security are divided into small manageable groups consisting of black hat and white hat team. The former will try to find and expose vulnerabilities in a wireless network while the latter will try to prevent such attacks on their wireless networks using hardware, software, design and enforcement of security policy and etc. This paper will try to demonstrate whether this approach will result in a more fruitful outcome in terms of students concept and theory understandings and motivation to learn.